Fair and Square: Impact of Hospitality Employees’ Justice Perceptions and Job Embeddedness on Citizenship Behavior during COVID-19 - Chhabra, Bindu; Mishra, Manit (Organizations and Markets in Emerging Economies, 2022)
COVID-19 pandemic has adversely impacted all industries, and the hospitality sector has been the worst hit. Drawing upon conservation of resource (COR) theory, it was hypothesized that organizational justice as well as job embeddedness will positively impact employees’ engagement in organizational citizenship behavior (OCB). In addition, the moderating role of job embeddedness in organizational justice–OCB relationship was studied. Using time-lagged data of hospitality employees from India, the results demonstrate that of all dimensions of organizational justice, interactional justice emerges as the strongest predictor of OCB. Further, job embeddedness was seen to have a significant relationship with all dimensions of OCB. Support was also found for the moderating role of job embeddedness in strengthening the positive relationship between justice perceptions and certain dimensions of OCB. Finally, the implications are discussed enhancing our understanding of organizational justice—job embeddedness—OCB relationship in Indian hospitality sector during the COVID-19 pandemic, suggesting several measures which can be taken by managers of this sector to promote employee extra role behaviors.